Reading La Barka within the Perspective of Feminist Stylistics - Mytha Candria (Program Studi Ilmu Perpustakaan, Fakultas Ilmu Budaya, Universitas Diponegoro, 2020)
This article presents a feminist stylistic analysis of religion in Nh. Dini’s novel La Barka. Proposed by Sara Mills in 1995, feminist stylistics aims to uncover gender bias in both written and spoken (literary) texts; feminist stylistics differs from other stylistic analyses in that it studies the context of text production and the context of text reception so as to reveal hidden sexist ideologies. (Literary) text production includes seven (7) factors, i.e. general language/ discourse constraints, textual antecedents, literary conventions, current literary trends, affiliations, publishing practices and sociohistorical factors. (Literary) text reception covers five (5) factors, which are intended audience, actual audience, implied reader, sociohistorical factors, and actual reader/s. Feminist stylistic reading of La Barka suggests that stereotypes of good women, as were prescribed by Indonesian New Order ideology and patriarchal Javanese traditions, do exist in the novel. Yet, there are also stereotypes of a good man; gentle, honest, assertive, independent, persistent, and tough are characters of good men, husbands, and fathers. Dini, however, does not just echo commonly accepted prescriptions of good women and men. She questions patriarchy, and religion is one social structure that she questions. Religion is sexist in that it does not properly educate women; it educates women in those skills necessary for housekeeping only. Also, religion does not accommodate women’s voices and needs, for all religious leaders are men, who are unwilling to seriously address women’s needs. Then Dini questions the hypocritical and uncritical attitudes of many religious believers; they observe religious rituals willingly and regularly but do not actualize the values in life.